Cover Image: Integrated mRNA and miRNA expression profile analyses reveal the potential roles of sex‐biased miRNA‐mRNA pairs in gonad tissues of the Chinese concave‐eared torrent frog (Odorrana tormota). J Exp Zool (Mol Dev Evol) 3–4/2019. Issue 3 (17th May 2019) - Shu, Yilin; Zhang, Huijuan; Cai, Qijia; Tang, Dong; Wang, Gang; Liu, Ting; Lv, Bihua; Wu, Hailong
Abstract : ON THE COVER : The cover image is based on the Research Article Integrated mRNA and miRNA expression profile analyses reveal the potential roles of sex‐biased miRNA‐mRNA pairs in gonad tissues of the Chinese concave‐eared torrent frog (Odorrana tormota) by Yilin Shu et al., https://doi.org/10.1002/jez.b.22851 . Cover image © Yilin Shu.